Implementation of Discovery Learning Theory in Science Learning in Madrasah Ibtidaiyah - Parinduri, Ahmad Nawawi; Salsabila, Syifa; Sutini, Sutini (Jurnal Pengabdian Nusantara, 2025)
This study examines the implementation of the discovery learning theory in science education at Madrasah Ibtidaiyah (MI) and its impact on improving students' science skills. The research method used is library research by reviewing various literature sources such as books, journals, and relevant scientific articles. The findings indicate that the application of discovery learning is capable of enhancing students' science process skills, such as observation, classification, hypothesis formulation, and conclusion drawing. The implementation of this method is carried out through exploration activities, simple experiments, group discussions, and reflections tailored to the characteristics of students at MI. However, the implementation of discovery learning faces challenges such as limited facilities and infrastructure, varying teacher competencies, limited learning time, and diverse student abilities. To overcome these obstacles, strengthening strategies are needed, such as teacher training, the development of simple and contextual learning media, support from school leaders, as well as the integration of technology and parental involvement in the learning process. In conclusion, discovery learning is an effective approach to enhancing students' science skills in MI, provided it is supported by various comprehensive and sustainable supporting factors.